Bird survey at Sungai Dusun Wildlife Reserve, Perak, Malaysia - Nur Aida Md Tamrin (2022)
A survey on birds was conducted at Sungai Dusun Wildlife Reserve on the 26th until 31th of October 2009. Ten mist nets were deployed throughout the four days sampling period. A total of 27 individuals representing 16 species from 10 families of birds were recorded. The most common species recorded is the Arachnothera longirostra that was represented by six individuals.